The Global FDI Network : Searching for Ultimate Investors - Damgaard, Jannick (IMF Working Papers; Working Paper ;, 2017)
This paper addresses three types of geographical decoupling in foreign direct investment (FDI), id est, challenges when using traditional FDI data as a proxy for real economic integration between economies: (i) large bilateral asymmetries between inward and outward FDI, (ii) the role of special purpose entities (SPEs), and (iii) the effect of moving from immediate counterpart to ultimate investing economy (UIE). A unique global FDI network is estimated, where SPEs are removed and FDI positions are broken down by the UIE. Total inward FDI in the new network is reduced by one-third, and financial centers are less dominant.